2009
DOI: 10.1111/j.1600-079x.2009.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents capacitation and apoptotic‐like changes of ram spermatozoa and increases fertility rate

Abstract: We recently demonstrated the presence of melatonin in ram seminal plasma and differences in its concentration in this fluid between the breeding and nonbreeding season. In this study, we investigate the hypothesis that in vitro treatment with melatonin affects ram sperm quality, and that this is reflected in the in vitro fertilization (IVF) results. Semen from nine rams was collected during the nonreproductive season and treated with 1 mum, 10 nm and 100 pm melatonin. Samples were incubated at 39 degrees C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
116
3
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(146 citation statements)
references
References 67 publications
20
116
3
3
Order By: Relevance
“…However, PEN was unable to maintain low levels of agglutination at the higher dose of 10% sheep serum. Since 2% sheep serum in SOF is commonly used for ram sperm IVF (Morton et al 2005b, Casao et al 2010 it would be interesting to assess if the agglutination status of ram spermatozoa in the fertilising medium influences the outcome of ovine IVF.…”
Section: Discussionmentioning
confidence: 99%
“…However, PEN was unable to maintain low levels of agglutination at the higher dose of 10% sheep serum. Since 2% sheep serum in SOF is commonly used for ram sperm IVF (Morton et al 2005b, Casao et al 2010 it would be interesting to assess if the agglutination status of ram spermatozoa in the fertilising medium influences the outcome of ovine IVF.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that melatonin significantly induced sperm hyperactivation (Si and Olds-Clarke, 2000;Fujinoki, 2008). Recently, it had been demonstrated that melatonin has beneficial direct role on the other sperm characteristics like capacitationand fertilization rates (Casao et al, 2010). Furthermore, melatonin and its metabolites potently scavenge ROS (Tan et al, 2007), thus altering redoxsensitive events and preventing oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the perusal of literature, no reports on inclusion of MEL on mobility and velocity parameters in mithun species and this is the primary report to our the best of knowledge. Earlier workers reported that MEL has significantly higher benefit on refrigerated preservation mammalian sperm and also enhanced the velocity and mobility parameters in the present study (Ashrafi et al, 2011;Ashrafi et al, 2013;Du Plessis et al, 2010) and also on semen quality parameters (Casao et al, 2009;Ashrafi et al, 2011;Hyun-Yong et al, 2006;Ashrafi et al, 2013;Du Plessis et al, 2010;Perumal et al, 2013;Perumal et al, 2015).…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, MEL has also potency two times as like of vitamin E in reaction against free radicals and reactive oxygen species (Pieri et al, 1994). The effect of anti-oxidant, MEL on ram (Casao et al, 2009;Ashrafi et al, 2011), boar (Hyun-Yong et al, 2006;Martin-Hildago et al, 2011), bull (Ashrafi et al, 2013); mithun Perumal et al, 2015), human (Du Plessis et al, 2010) and buffalo sperm (Li et al, 2012) revealed that it improves sperm mobility and velocity parameters of sperm in liquid storage. Perusal of literatures revealed that no information on the effect of MEL on the mobility and velocity parameters measured by CASA during liquid storage for extended period in mithun species.…”
Section: Introductionmentioning
confidence: 99%